Upcycling waste glass bottles as a binder within engineered cementitious composites (ECCs): Experimental investigation and environmental impact assessment - Avik Kumar Das; Jiacheng Xiao (Cleaner Materials)
Single-use waste glass bottles (WGB) pose significant environmental challenges in urban areas, and this study explores their upcycling into powdered glass (GP) as a supplementary cementitious material (SCM) in engineered cementitious composites (ECCs). Through, systematic investigation of their mechanical performance, durability, early age properties and shrinkage for different levels of GP replacement a sustainable ECC mix (GP-ECC) was developed. GP-ECC demonstrates excellent mechanical and durability performance, including high ductility (∼4%), tensile strength (∼4 MPa), narrow crack widths (∼60 μm), and manageable shrinkage (∼1700 με). Optimal results were observed at 20–30 % GP replacement, where improved particle packing and pozzolanic activity enhanced performance. In contrast, at higher replacement levels (50 %) led to increased porosity and reduced durability due to suppressed hydration. The inclusion of natural seawater further accelerated early hydration and strength gain, though slight compromises were noted in crack control due to ionic interference, overall their performance are comparable to GP-ECC. Microstructural analyses (SEM, XRD) confirmed denser matrices and stronger fiber–matrix bonding at 30 % GP, particularly in seawater-mixed ECCs thereby, confirming the feasibility and high-perfromance of sea based materials (SBM)-GP-ECCs. A novel framework for life cycle analysis (LCA) for ECCs considering regional variations, including transportation emissions and energy mix, thereby reflecting intercity differences. GP-ECC and SBM-GP-ECC mixes achieved notable reductions in CO2 (∼8–10 %) emission and costs other ecological impacts, but such effects is a function of the location outperforming normal concrete and GP-concrete by up to 100x in tensile and durability properties. By systematically evaluating mechanical, rheological, durability, and microstructural properties, this study establishes a robust foundation for future research and practical deployment of GP-marine ECCs derived from waste materials, contributing to circular economy strategies and the development of cleaner, high-performance construction materials.